Religious Sciences in the Great Mosque of Cordoba: Its Curricula, Scholars, and Students in Era of Caliphate - Al Naqbi, Sami; Al-Leheabi, Saleh (Al-Adab Journal, 2025)
There were mosques and mosques in various Islamic regions and regions in the Levant, Iraq, Egypt, Morocco, and Andalusia served as scientific and educational institutes and schools, as well as religious ones. Muslim scholars and jurists found the mosque to be the most appropriate place to study the book of Allah and the various religious sciences associated with it, due to the status and sanctity of the mosque among all Muslims. Some mosques and mosques became more like scientific universities from which many scholars, jurists and thinkers graduated, whose fame spread throughout the Islamic world. The Great Mosque in Cordoba was one of those beacons. The scientific and educational sciences that the Islamic world knew, as it was a scientific university to which students of science and knowledge flocked from various parts of the Islamic world and the European West, and various branches of science and basic knowledge were taught there, such as Islamic sciences such as legislation, interpretation, jurisprudence, the Prophet’s hadith, and other experimental and rational sciences, and many other experimental and rational sciences have emerged. Andalusia jurists who taught these sciences at the Great Mosque in Cordoba and who contributed to the progress and development of these sciences and their dissemination among the various groups of Andalusia society, as well as the graduation of a large number of students of science and knowledge specialized in religious sciences, who contributed to the spread of science and knowledge in various people thanks to the science and knowledge they received in this mosque.